Why the integration of demographic and site-based studies of disturbance is essential for the conservation of jarrah forest fauna - Wardell-Johnson, Grant; Calver, M.; Saunders, D.; Conroy, S.; Jones, B. (Royal Zoological Society of New South Wales, 2004)
We review recent studies of the impacts of disturbance on the fauna of the jarrah forest, southwestern Australia. In particular, we examine five case studies that provide alternative approaches to researching disturbance impacts. Assessing site-based studies of patterns of fire regimes lead us to argue that point measures of frequency are inadequate to understand scale and pattern across landscapes. Rather, extrapolating from site-based data to draw conclusions on landscape-scale changes may obscure fine-scale heterogeneity in disturbance, which is critical to the conservation of biodiversity. We review species-based studies and conclude that assessments of demographic trends are more effective than surveys in determining impacts, and providing early warning of declines because they highlight threatening processes. Furthermore, risk analysis, when critical aspects of the biology of participating species are weakly known, may lead to misclassification of species and poor decisions on conservation priorities. The review of recent impact studies of logging on jarrah forest fauna demonstrates that logging interacts with predation by foxes to threaten arboreal mammals. Hence, measures to protect threatened vertebrates benefit many species. However, while concentrating on proximate causes of fauna decline produces immediate conservation gains, long-term conservation requires an understanding of both proximate and ultimate causes and their interaction. We urge the acquisition of reliable, site-based demographic data that allows predictive modelling for species, and hence testing of alternative hypotheses regarding impact, distribution and decline. We also seek the integration of data and approaches to enable landscape-scale patterns to be discerned and interpreted for effective conservation planning.